Faktor Jenis Kelamin dan Status Imunisasi terhadap Kejadian Pneumonia pada Balita di RSUD dr. Soedarso - Lilis Sri Supiatun Mamesah; Isnin Anang Marhana; Zera Qurrota A'yuni (Jurnal Bidan Cerdas, 2022)
Introduction: The incidence of pneumonia in toddlers was recorded as the second highest case in the Pediatric Inpatient Room at the dr. Soedarso Regional General Hospital, West Borneo Province. Purpose: Analyzing the relationship between sex and immunization status on the incidence of pneumonia in toddlers at the dr. Soedarso Regional General Hospital, West Borneo Province. Methods: The study used a case control design with 31 cases and 31 controls. Sampling using a total sampling technique with a ratio of 1:1. The case group was toddlers diagnosed with pneumonia by the Patient Responsible Doctor who was recorded in the medical record. The control group was toddlers were not diagnosed with pneumonia by the Patient Responsible Doctor who was recorded in the medical record . This study used bivariate analysis. The statistical test is the Chi-Square Test. Results: The most data for toddlers is owned by toddlers with male sex (54.8%).Most of the data for toddlers is owned by toddlers with incomplete immunization status (82.3%). The results of the bivariate analysis showed that there was no significant correlation between sex and immunization status on the incidence of pneumonia in toddlers. Conclusion: There was no significant correlation between sex and immunization status on the incidence of pneumonia in toddlers at the dr. Soedarso Regional General Hospital, West Borneo Province. This research still needs further research to explore other factors that can cause pneumonia in toddlers.